Psychological Outcomes Associated with Stay-at-Home Orders and the Perceived Impact of COVID-19 on Daily Life. (July 2020) - Tull, Matthew T.; Edmonds, Keith A.; Scamaldo, Kayla M.; Richmond, Julia R.; Rose, Jason P.; Gratz, Kim L.
Highlights: Examined impact of COVID-19 and stay-at-home orders on psychological outcomes. Stay-at-home orders linked to health anxiety, financial worry, and loneliness. Impact of COVID-19 on life associated with health anxiety and financial worry. Impact of COVID-19 on life associated with less loneliness and more social support. Results highlight importance of social connection and need for tele-mental health. Abstract: The COVID-19 pandemic has resulted in the widespread implementation of extraordinary physical distancing interventions (e.g., stay-at-home orders) to slow the spread of the virus. Although vital, these interventions may be socially and economically disruptive, contributing to adverse psychological outcomes. This study examined relations of both stay-at-home orders and the perceived impact of COVID-19 on daily life to psychological outcomes (depression, health anxiety, financial worry, social support, and loneliness) in a nationwide U.S. community adult sample (N = 500; 47% women, mean age = 40). Participants completed questionnaires assessing psychological outcomes, stay-at-home order status, and COVID-19's impact on their daily life. Being under a stay-at-home order was associated with greater health anxiety, financial worry, and loneliness. Moreover, the perceived impact of COVID-19 on daily life was positively associated with health anxiety, financial worry, and social support, but negatively associated with loneliness. Findings highlight the importance of social connection to mitigate negative psychological consequences of the COVID-19 pandemic.